Constructing a desired nanofibril network morphology for stretchable polymer films by weakening the intermolecular interaction of a conjugated polymer in an elastomer matrix and extending the film-forming time. Issue 6 (26th January 2023) - Zhang, Tao; Liu, Yadi; Zhang, Lu; Wang, Sichun; Li, Junhang; Zuo, Jiaming; Yu, Xinhong; Zhang, Qiang; Han, Yanchun
Abstract : Low R a(b) solvent o -DCB weakens intermolecular interactions of N2200 in the SEBS matrix, leading to the formation of a nanofibril network morphology with a small fibril size (<45 nm), which greatly improves the stretchability of the blend film. Abstract : A desired phase-separated morphology of interconnected polymer nanofibrils in an elastomer matrix is crucial for keeping the electrical properties under strain in conjugated polymer-elastomer blend systems. However, how to reduce the fibril size by controlling the solution aggregation and film-forming kinetics remains unclear. Herein, we propose a strategy to induce an interpenetrating nanofibril network morphology with a small fibril size through weakening the intermolecular interactions and extending the film-forming time of P(NDI2OD-T2) (N2200) in an elastomer polystyrene- block -poly(ethylene-ran-butylene)- block -polystyrene (SEBS) matrix. This was enabled by using a low Hansen solubility parameter distance of the N2200 backbone ( R a(b) ) and high boiling point solvents, such as 1, 2-dichlorobenzene ( o -DCB, R a(b) = 8.58 MPa 1/2 ) to dissolve the blend. The weak intermolecular interaction of N2200 in o -DCB suppresses the self-aggregation of N2200 in solution. Meanwhile, the long film-forming process ensures the slow but continuous growth of N2200 aggregates. Eventually, a sandwich-like vertical phase separation structure with N2200 enriched at both the top and bottom surfaces is obtained, where the N2200 layer comprises nanofibrils with a small fibril diameter (<45 nm) to form a continuous network. Under tensile stress, these nanofibrils can freely rotate and align along the stretching direction. Meanwhile, the polymer chains in the N2200 crystal regions can slip to a greater degree within the SEBS matrix. These features ensure effective dissipation of strain energy through the SEBS matrix and provide sufficient percolation channels for charge transport. The mobility of the resulting blend film gradually increases from 0.11 to 0.26 cm 2 V −1 s −1 at 100% strain and exhibits negligible loss as strain increases to 150%. The COS of the blend film can reach 153%, while high R a(b) solvents such as toluene (Tol) lead to the formation of nanofibril bundles with a large size (diameter: >230 nm). Though they are favorable for charge transport, the wide bundles have greater brittleness and are prone to breaking under strain. The mobility of the blend film processed by Tol decreases continuously from 0.15 to 0.04 cm 2 V −1 s −1 at 150% strain.